2020
DOI: 10.1088/2515-7620/ab716d
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned aerial vehicle observations of cold venting from exploratory hydraulic fracturing in the United Kingdom

Abstract: Unmanned aerial vehicle (UAV) surveys allow for rapid-response near-field sampling, downwind of emission sources, such as gas extraction sites, without the need for site access. UAVs can be used in emission source identification alongside instantaneous flux estimation. A UAV was used to sample downwind of the UK's first and only gas extraction site to use exploratory onshore horizontal hydraulic fracturing (fracking) of shale formations, in Little Plumpton, Lancashire. In-situ calibrated UAV methane mole fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…The peak flux values for each of the three methods were all in agreement with each other and with the operator reported peak gas flow, within 1σ uncertainty. These values were also in excellent agreement with fluxes calculated from four UAV surveys, which reported instantaneous emission fluxes within a range of 9 to 156 g s −1 on 14 January (Shah et al 2020a). The total CH 4 mass estimates were also in good agreement with each other, within their respective uncertainties (at 1σ).…”
Section: Ch 4 Flux Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The peak flux values for each of the three methods were all in agreement with each other and with the operator reported peak gas flow, within 1σ uncertainty. These values were also in excellent agreement with fluxes calculated from four UAV surveys, which reported instantaneous emission fluxes within a range of 9 to 156 g s −1 on 14 January (Shah et al 2020a). The total CH 4 mass estimates were also in good agreement with each other, within their respective uncertainties (at 1σ).…”
Section: Ch 4 Flux Resultssupporting
confidence: 86%
“…Summary of peak and mean CH 4 fluxes, and total CH 4 mass emitted, as calculated by three different flux estimation methods. UAV measured fluxes derived from mobile surveys are also provided (seeShah et al 2020a for more information) alongside the operator/regulator reported flux and total CH 4 mass estimates.…”
mentioning
confidence: 99%
“…Other survey platforms, such as unmanned aerial vehicles (UAVs) also offer potential for CH4 flux quantification from numerous sources (e.g. Nathan et al, 2015;Yang et al, 2018;Allen et al, 2019;Shah et al, 2020;Shaw et al, 2021). For an interesting overview…”
Section: Discussionmentioning
confidence: 99%
“…Air is sampled through a tube (often referred to as a tether) carried by the UAV and measured by an instrument on the ground (e.g. [ 34 , 38 , 65 ] and figure 2 ). This method allows for the beneficial use of high-performance ground-based instrumentation which would otherwise be impossible for a UAV to carry, and which can also be operated continuously.…”
Section: Methane Measurement Approachesmentioning
confidence: 99%
“…Such a heavy payload will only be useful when using larger, sturdier UAVs with maximum take-off weights greater than 20 kg, however. A prototype of a miniaturized off-axis integrated cavity output spectrometer (3.4 kg, 32 W, 2 ppb at 1 Hz precision) built specifically for UAV use was tested on a rotary-wing UAV and successfully used to calculate methane fluxes [ 38 , 65 ]. Similarly, an open-path cavity ring-down spectroscopy instrument (4.1 kg) was successfully integrated onboard a rotary-wing UAV, demonstrating in-flight precisions of between 10 and 30 ppb [ 77 ].…”
Section: Methane Measurement Approachesmentioning
confidence: 99%